2015
DOI: 10.1177/0003319715579781
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mean Platelet Volume in Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a genetic disorder of lipoprotein metabolism and increases the risk of premature cardiovascular diseases. In patients with FH, platelet function may be activated; however, the extent of this activation and its etiology are unclear. We aimed to evaluate the mean platelet volume (MPV), a marker of platelet activation, in patients with FH. The study group consisted of 164 patients with FH and 160 control patients. Controls were matched for age, gender, hypertension, and smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
0
15
1
1
Order By: Relevance
“…Previous study showed that MPV is increased in patients with FH and that is independently associated with total cholesterol level [25]. platelet cholesterol (PC) can be correlated with serum LDL-C Here we could not find any differences between MPV in FH and control, the different control groups can explain our different results as in the previous study the control was the norm lipid population, however in both studies the platelet count was significantly difference between groups.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous study showed that MPV is increased in patients with FH and that is independently associated with total cholesterol level [25]. platelet cholesterol (PC) can be correlated with serum LDL-C Here we could not find any differences between MPV in FH and control, the different control groups can explain our different results as in the previous study the control was the norm lipid population, however in both studies the platelet count was significantly difference between groups.…”
Section: Discussioncontrasting
confidence: 69%
“…The MPV is an important platelet indicator and as a marker of platelet size and activation. High MPV value is explained by a biologic explanation that larger platelets are more active in metabolic and enzymatic manner and tend to aggregate, resulting in thrombus or endothelial dysfunction than smaller platelets, as more and more research has been found that MPV is associated with prehypertension and hypertension (Varol et al ., ), type 2 diabetes (Chen et al ., ), familial hypercholesterolemia (Icli et al ., ), cancers (Kemal et al ., ; Kumagai et al ., ; Li et al ., ; Yu et al ., ), and many vascular diseases. Briefly, many studies have found that MPV associate with many vascular complications by means of endothelial damage and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that MPV was independently associated with total cholesterol level. In their study, Icli et al have shown that MPV was increased in patients with familial hypercholesterolemia and that it was independently associated with total cholesterol level [28]. As is known, increased total cholesterol levels increase the risk of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 92%